A survey of the literature on managing capital inflows - Masahiro Kawai; Shinji Takagi (Asian Development Bank Institute (ADBI), 2008)
How to manage capital inflows remains an important policy issue for many emerging market economies. This paper presents a brief survey of the literature on managing capital inflows, with a focus on developing and emerging market economies. The paper, after discussing the economic characteristics of capital inflows, provides an overview of the evolution of thinking on capital account liberalization, the use of capital controls as an instrument of managing capital inflows, and the effectiveness and limitations of conventional macroeconomic and structural instruments. Although the literature is still evolving, it provides little practical guidance on capital account liberalization. For those countries facing a surge in capital inflows, consensus seems to be that, aside from learning to live with an appreciating (and fluctuating) currency, and strengthening the financial system, there is no effective and sustainable policy measure either to reduce the size of inflows or to prevent the adverse consequence of such inflows. Additional work is especially needed to develop tools to identify and quantify the various risks of capital inflows.
Keywords: F21; F32; F34; 330; Kapitalimport; Kapitalverkehrspolitik